Modelling of bicycle transport in OTM - Tønning, Anders; Vuk, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
Traffic models play essential part in decision making when it comes to infrastructure investments. Danes traditionally bicycle a lot, especially in cities. For instance, in Copenhagen more than 60% of all commuting trips are done on bicycle. The Copenhagen Municipality has accordingly made large investments in the bicycle infrastructure since 2010. In order to support those investments it has been necessary to improve the bicycle modeling in the operational traffic model for Copenhagen, the OTM model. The primary tasks in the project were to create a new route choice model for bicycling, and to estimate a new demand model. These tasks are nearly completed and the achieved findings are described in the paper. In summary, we found that bicycle route choice depends on congestion on biking paths, surroundings (e.g. green areas), hilliness, and street crossings, while the demand for biking depends on parameters of the prechosen route and the bicyclist’s socio-economic background.